Analysis of barriers to the implementation of energy efficiency actions in the production of ceramics in Colombia. (15th January 2018) - Manrique, Raiza; Vásquez, Daniela; Vallejo, Gabriel; Chejne, Farid; Amell, Andrés A.; Herrera, Bernardo
Abstract: A characterization of the energy profile of certain ceramic industry enterprises in Colombia was carried out. An emphasis was placed on the barriers that prevent the implementation of energy efficiency actions, the degree of obsolescence of their production equipment, and the potential for energy efficiency savings. The barrier with the greatest impact in this sector was found to be hidden costs, followed by corporate values . There was a positive correlation between the potential savings and the degree of equipment obsolescence and the total barrier factor to the implementation of energy efficiency measures. Finally, it was concluded that the creation of programs that allow for more certainty in the appropriation of new technologies could help to overcome the barriers in Colombia's ceramic industry. Highlights: Energy diagnostics was performed to characterize the ceramic industry in Colombia. Barriers and technological obsolescence in the ceramic sector was quantified. The use of gasifiers and oxy-fuel systems are proposed as good practice.